FEATURES OF CONSTRUCTION OF MODELS OF IDEOLOGY LIBRARY COMMUNITY - Yakubenko, Yaroslav A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
An important element in the course of constructing a model of ideology is the analysis of the main trends of the library in terms of socio-economic changes, the ratio of the main factors determining the dynamics of the process. This approach makes it possible to solve one major problem with the selection of study basic features that should meet an imaginary model library.